Current Issues in Sports and Exercise Medicine - Hamlin, Michael; Draper, Nick; Kathiravel, Yaso (IntechOpen, 2013)
This unique resource presents current issues in sports and exercise medicine which outlines new areas of knowledge and provides updates on current knowledge in the broad field of sports and exercise medicine. Written by experts in their own sub-disciplines, Current Issues in Sports and Exercise Medicine discusses the physiology behind sports injuries and presents new and exciting approaches to manage such injuries. In addition, the book explores the relationship between exercise, health and performance by providing new information in areas such as exercise and immunity, the use of iron supplementation for performance, how exercise affects reactive oxygen species, and the proposed benefits of real and simulated altitude training. This book is well referenced and illustrated and will be a valuable resource for sports medicine specialists, physiologists, coaches, physical conditioners, physiotherapists and graduate and medical school students.